Studi Formulasi Hand Body Lotion Ekstrak Etanol Kunyit (Curcuma domestica val.) - Ningsih, Arista Wahyu; Klau, Irvan Charles S.; Wardani, Eka Pramuda (Universitas PGRI Adi Buana, Surabaya, 2021)
Damage to the skin will seriously affect human health and appearance, so the skin needs to be protected and maintained in good health. Kunyit (Curcuma domestica Val.) Which contains antioxidants can be processed into a product and used to solve the problems of people who live in tropical climates, such as problems with the skin due to frequent exposure to sunlight and causing free radicals. It is hoped that the development and processing of kunyit in Indonesia will increase, given that this product has many benefits and advantages in terms of health and economic value. The research method used was Curcuma Rhizoma simplicia extraction, Kunyit extract Hand Body lotion formulation, Kunyit extract Hand Body lotion hedonic test, and Kunyit extract Hand Body lotion Moisture Test. Based on the results of the organoleptic observation test, the formulation has a distinctive smell of turmeric, thick and yellow in color. In the favorite test of the Kunyit Extract Hand Body lotion, 75 percent of the panelists liked the color, 65 percent of the panelists liked the aroma, 66 percent of the panelists liked the texture, and 69 percent of the panelists liked the non-sticky impression. The percentage of humidity obtained from the panelists on average was 77 percent and it was included in the very humid category